Konstruksi Asumtif Sayyid Quthb Terhadap Wacana Naskh Dalam Tafsir Fi Dzhilal Al-Qur'an - Ahmad Falhan (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
This article describes the concept of naskh understood by Sayyid Quthb. He acknowledged the existence of the text, but it did not make the verse dysfunctional. The method used in this paper is a library research method that explores various sources to be used as data in processing conclusions. This paper concludes that the assumption built by Sayyid Quthb is that some verses of the Qur'an can interpret others (yufassiru ba'duha ba'da). He succeeded in reconciling a number of verses that were claimed to have undergone a textual process. The message of the Koran is something that is integral and systemic in nature. The texts that are recognized for their existaence are tasyri'i texts, which do not experience inter-verse texts and takwiniy texts, which can occur as a form of God's intervention in regulating human life.